Emerging Corporate Disclosure of Environmental Social and Governance (ESG) Risks: An Australian Study - Chitra S de Silva Lokuwaduge; Keshara de Silva (Australasian Accounting, Business and Finance Journal, 2020)
Today, companies across all industries around the globe face the challenges of unprecedented disruption due to climate change and other social disruptions. It is the responsibility of standard setters and regulators of the financial sector to constantly encourage industries to adopt and respond instead of ignoring the disruption. Environmental Social and Governance (ESG) risk disclosure is one of the main emerging corporate disclosures of rising importance. Specifically with new Australian Securities Exchange (ASX) listing rules companies listed in the ASX are expected to comply with new Environmental Social and Governance (ESG) risk discloser requirements from the year 2016 and if they do not comply, the 'if not, why not' rule applies. This study seeks to provide insight into the current ESG risk disclosure practices in the Australian context giving particular reference to the extractive sector companies for which ESG disclosure has become a crucial reporting requirement.
Keywords: Environment; ESG risk disclosure; ' if not; why not' sustainability; investors; stakeholders.